Existence of Solutions for Generalized Vector Quasi-Equilibrium Problems by Scalarization Method with Applications - De-ning Qu; Cao-zong Cheng (Abstract and Applied Analysis)
The aim of this paper is to study generalized vector quasi-equilibrium problems (GVQEPs) by scalarization method in locally convex topological vector spaces. A general nonlinear scalarization function for set-valued mappings is introduced, its main properties are established, and some results on the existence of solutions of the GVQEPs are shown by utilizing the introduced scalarization function. Finally, a vector variational inclusion problem is discussed as an application of the results of GVQEPs.